Changes in lipids and inflammation in adults with super-refractory status epilepticus on a ketogenic diet - Dickens, Alex M.; Johnson, Tory P.; Lamichhane, Santosh; Kumar, Anupama; Pardo, Carlos A.; Gutierrez, Erie G.; Haughey, Norman; Cervenka, Mackenzie C. (Frontiers in Molecular Biosciences, 2023)
Introduction: To test the hypothesis that increased ketone body production with a ketogenic diet (KD) will correlate with reductions in pro-inflammatory cytokines, lipid subspecies, and improved clinical outcomes in adults treated with an adjunctive ketogenic diet for super-refractory status epilepticus (SRSE). Methods: Adults (18 years or older) were treated with a 4:1 (fat:carbohydrate and protein) ratio enteral KD as adjunctive therapy to pharmacologic seizure suppression for SRSE. Blood and urine samples and clinical measurements were collected at baseline (n=10), after 1 week (n=8), and after 2 weeks of KD (n=5). Urine acetoacetate, serum β-hydroxybutyrate, lipidomics, pro-inflammatory cytokines (IL-1β, IL-6), chemokines (CCL3, CCL4, CXCL13), and clinical measurements were obtained at these 3 time points. Univariate and multivariate data analyses were performed to determine the correlation between ketone body production and circulating lipids, inflammatory biomarkers, and clinical outcome.Results: Changes in lipids included an increase in ceramides, mono-hexosyl ceramide, sphingomyelin, phosphocholine, and phosphoserines, and there was a significant reduction in proinflammatory mediators IL-6 and CXCL13 seen at 1 and 2 weeks of KD. Higher blood βhydroxybutyrate levels at baseline correlated with better clinical outcome however, ketone body production did not correlate with other variables during treatment. Higher chemokine CCL3 levels following treatment correlated with greater length of intensive care unit stay, higher modified Rankin Scale score (worse neurologic disability) at discharge and 6-month follow up. This is a provisional file, not the final typeset article Discussion: Adults receiving an adjunctive enteral ketogenic diet for super-refractory status epilepticus have alterations in select pro-inflammatory cytokines and lipid species that may predict response to treatment.